Market Index Return and Volatility Spillovers Evidence from Arabian Stock Markets - AL-Naif, Khaled; Malahim, Sari; Atieh, Musa (Jordan Journal of Economic Sciences, 2021)
This study aims to examine the index return variation caused by shocks transmissions among six Arabian stock markets namely (Amman stock exchange, Casablanca stock exchange, Dubai financial market, Egypt Capital Market, Saudi Stock Market, and Palestine Securities Exchanges) throughout the 2nd of January 2017 and the 2nd of January 2020. The results showed weak returns and volatility spillovers within the Arabian stock markets; in particular, the overall spillover index of return indicates that only 3.38% of the variations are caused by the cross-market shocks, whereas, 96.62% of the variations are caused by the market's shocks.In addition, the overall value of the volatility spillover index implies that only 2.4% of the variations are caused by the cross-market shocks, whereas, 97.6% of the variations are caused by market own shocks.The study recommended conducting further studies on all Arabian markets, especially in light of the current conditions of the Corona crisis.